2022
DOI: 10.34172/aim.2022.05
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Count in Preterm Neonates With and Without Necrotizing Enterocolitis

Abstract: Background: Recently, blood monocyte concentration has been introduced as an inventive biomarker for necrotizing enterocolitis (NEC) in low birth weight neonate; therefore, we aimed to examine and compare blood monocyte counts in preterm neonates with and without NEC. Methods: A case-control study was conducted on 160 preterm neonates in Tehran during 2017. In this study, medical records and laboratory findings of 80 neonates with NEC (case) and 80 neonates (control), who were randomly chosen from among neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…Next, the authors also found that the more severe the NEC stage, the lower AMC and the greater the reduction of AMC at the onset. In the present study, there were statistical differences between stage 1 and stage 2, stage 1 and stage 3, but there was no statistical difference between stage 2 and stage 3, which was different from the results of Desiraju et al 23 and Tajalli et al 14 At recovery, AMC was highest in stage 3, followed by stage 2, and lowest in stage 1, although there was no statistical difference.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Next, the authors also found that the more severe the NEC stage, the lower AMC and the greater the reduction of AMC at the onset. In the present study, there were statistical differences between stage 1 and stage 2, stage 1 and stage 3, but there was no statistical difference between stage 2 and stage 3, which was different from the results of Desiraju et al 23 and Tajalli et al 14 At recovery, AMC was highest in stage 3, followed by stage 2, and lowest in stage 1, although there was no statistical difference.…”
Section: Discussioncontrasting
confidence: 99%
“… 11 When intestinal inflammation occurs, blood monocytes, as the only source of intestinal monocyte-derived macrophages, need to migrate extensively to the gut. 12 , 13 Meanwhile, in infants with NEC, the absolute monocyte counts (AMC) decreased in varying degrees, 11 , 14 , 15 also associated with mortality in NEC. 16 The activation of monocytes participates in the development of NEC, 17 , 18 and blocking NF-κB activation in Ly6c + monocytes alleviates NEC.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting the severity of NEC in preterm neonates is crucial for timely intervention and management [6]. The monocyte count, which is a type of white blood cell, has been investigated as a potential biomarker for predicting the severity of NEC [1].…”
Section: Discussionmentioning
confidence: 99%
“…NECROTIZING enterocolitis (NEC) is one of the most serious and common gastrointestinal medical/ surgical emergencies in preterm neonates, which affects 6%-7% of extremely low birth weight neonates. NEC is one of the major causes of mortality in neonates born prior to 32 weeks of gestation or with birth weight less than 1500 grams [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation